Moral Hazard and Bargaining over Incentive Contracts - Marcus Dittrich; Silvio Städter (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyses bargaining over an incentive compatible contract in a moral hazard framework. We introduce the Kalai-Smorodinsky bargaining solution and compare the outcome with the commonly applied Nash solution. Whether worker's effort is higher in the Nash or the Kalai-Smorodinsky solution depends on the agents. bargaining power. If agents have equal bargaining power, the contract in the Kalai-Smorodinsky solution yields a more efficient outcome and induces more effort. The social planner can mitigate inefficiencies arising in both bargaining solutions from the moral hazard problem and even achieve the first-best outcome by allocating the agents' bargaining power. If raising the worker's bargaining power is necessary to achieve the first-best solution, this increase must be higher in the Nash solution than in the Kalai-Smorodinsky solution.
Keywords: C71; D82; J41; 330; incentive contracts; moral hazard; Nash bargaining solution; Kalai-Smorodinsky solution; bargaining power